2021
DOI: 10.20473/fmi.v55i1.24389
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Lower Limb Muscles and Body Mass Index with Body Balance in the Elderly

Abstract: Indonesia enters the ageing population because of increasing elderly population. The large number of ederly population can have negative impact if they have some problems, such as increased disability and increased rates of life dependence. Based on health research, it was mentioned that the cause of the most injuries to the elderly group is falls that are caused by balance disorder. Balance problems can be caused by changes of musculoskeletal function. In addition, Body Mass Index (BMI) is still a problem tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…One of the most crucial elements in reducing the elderly's risk of falling is physical activity (Chang et al, 2004;Gillespie et al, 2012). It has been demonstrated that setting training goals to increase balance, flexibility, and muscle strength can lower the number of falls among elderly residents of the community (Valentina, Kurniawati & Maramis, 2021;Gillespie et al, 2012). The Otago Exercise Program (OEP) is a multi-component exercise regimen created expressly to lessen the risk of falling in the elderly by improving balance and lower-extremity muscular strength (Binns & Taylor, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most crucial elements in reducing the elderly's risk of falling is physical activity (Chang et al, 2004;Gillespie et al, 2012). It has been demonstrated that setting training goals to increase balance, flexibility, and muscle strength can lower the number of falls among elderly residents of the community (Valentina, Kurniawati & Maramis, 2021;Gillespie et al, 2012). The Otago Exercise Program (OEP) is a multi-component exercise regimen created expressly to lessen the risk of falling in the elderly by improving balance and lower-extremity muscular strength (Binns & Taylor, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang juga dilakukan oleh Özçadirci, (2021) mengemukakan bahwa pada jenis kelamin laki-laki peningkatan kekuatan otot lebih baik daripada perempuan yang dikarenakan pekerjaan, olahraga, dan aktivitas yang membutuhkan kekuatan otot lebih besar daripada perempuan. Untuk index massa tubuh (IMT) sangat berpengaruh terhadap kekuatan otot tungkai seperti pada penelitian Valentina et al, (2021) yang meneliti dengan total subjek sebanyak 39 orang dengan nilai p = 0,607 (>0,05).…”
Section: Pembahasanunclassified
“…Selaras dengan Riskesdas, 2013 menyatakan bahwa persentase lansia yang mengalami jatuh oleh karena gangguan keseimbangan yaitu 49,5% pada kelompok usia 55-64 tahun, 67,1% pada kelompok usia 65-74, dan 78,2% pada usia lebih dari 75 tahun yang menunjukkan semakin bertambahnya usia maka mengakibatkan penurunan keseimbangan. 17 Umur juga terkait dengan perubahan pada lebar langkah saat berjalan khususnya pada permukaan menanjak. Hasil penelitian menunjukkan sampel termuda dengan umur 65 Tahun dan sampel tertua dengan umur 73 Tahun memiliki lebar langkah yang lebih besar atau tidak normal saat berjalan dipermukaan menanjak.…”
Section: Diskusi Karakteristik Responden Bersasarkan Usiaunclassified